The sustainability of microfinance institutions in South - Lekatsa, Teboho (Research of GSB, 2018)
Microfinance targets the poor and very poor, both in urban and rural areas. It has become a common method of poverty alleviation in many developing countries. Several microfinance institutions have adopted a social mission to eradicate poverty by providing credit to the poor. In the past, microfinance organizations used to focus on farmers in rural areas. Modern microfinance programs are focused on the population that is largely neglected by the formal financial sector, specifically women. Due to the perceived risk in this type of uncollateralized lending, private equity markets are not keen on financing microfinance institutions. Furthermore, microfinance institutions are seen as socially motivated as opposed to being financially motivated. For that reason, their profitability and sustainability has come under question in the last decade. Two approaches to the issue of sustainability exist. The dominant institutionist approach argues that microfinance institutions should focus on being sustainable as this will improve their chances of alleviating poverty. The welfarist approach disagrees with this view by arguing that focusing on sustainability will result in the neglect of the poorest of the poor. This study analyses the sustainability of microfinance in South Africa by using a case study research approach. The study explores the challenges to sustainability in South Africa. The results of the study indicate that the microfinance institutions are not profitable nor self- sufficient. The most notable challenge to this sustainability is the high personnel costs. South African MFIs experience higher operating costs than their African counterparts. The study also indicates that the more financially sound microfinance institutions have a lower level of depth outreach than the more subsidy dependent institutions.